CEO–TMT Congruence in Growth‐Need Strength and Firm Growth. (22nd March 2022) - Wan, Xue; Zhang, Stephen X.; Wei, Feng
Abstract: The literature on the CEO–TMT interface has called for research on the implications of CEO–TMT congruence or fit. We examine the effect of CEO–TMT degree of congruence, forms of congruence, and forms of incongruence in growth‐need strength on firm growth based on decades of research on leader–team congruence. Using five‐wave survey data from the CEOs and other TMT members of 128 new firms, we find CEO–TMT incongruence in growth‐need strength is negatively related to firm growth by reducing CEO openness to the TMT. Our study charts a new avenue for upper echelons research, particularly on the CEO–TMT interface, by providing a nuanced theoretical framework and evidence on CEO–TMT congruence.